The level of I-FABP and IgA/IgG to beta-lactoglobulin in mothers at risk for gestational diabetes and in their children: association with antibodies to Bifidobacterium adolescentis and Bifidobacterium breve - Vorobjova, Tamara; Tagoma, Aili; Peterson, Celeste; Talja, Ija; Bärenson, Anu; Alnek, Kristi; Janson, Helis; Metsküla, Kaja; Kirss, Anne; Sepp, Epp; Rööp, Tiiu; Kõljalg, Siiri; et al. (Frontiers in Immunology, 2025)
BackgroundThe mechanisms underlying gestational diabetes mellitus (GDM) and their impact on maternal and child immunity remain unclear. We hypothesize that gut microbiome alterations and increased small intestinal permeability contribute to GDM. Intestinal fatty acid-binding protein (I-FABP) leakage and elevated IgA/IgG against beta-lactoglobulin may indicate mucosal damage and may serve as biomarkers.MethodsThis study evaluated I-FABP and IgA/IgG levels against beta-lactoglobulin in mothers with and without GDM (n=100) and in their children (n=87 at time point 1 (TP1), n=79 at time point 2 (TP2). Levels of antibody to Bifidobacterium adolescentis (DSM20083, DSM20086) and Bifidobacterium breve (DSM20213) were assessed using flow cytometry. I-FABP was measured using the Hycult Biotech ELISA Kit, and IgA/IgG levels to beta-lactoglobulin were measured using in-house ELISA.ResultsI-FABP and IgA/IgG levels did not significantly differ between mothers with and without GDM. However, children at TP1 had significantly higher I-FABP, IgA and IgG levels to beta-lactoglobulin than their mothers (p<0.01). In children, both I-FABP and IgA levels to beta-lactoglobulin declined with age (p<0.05). The children of mothers with GDM had higher IgA levels to beta-lactoglobulin (p=0.004). I-FABP was inversely correlated with IgA to B. adolescentis in GDM mothers (p<0.002). Breastfeed children had higher beta-lactoglobulin IgA/IgG levels (p=0.02), but I-FABP levels did not differ regarding the length of breastfeeding.ConclusionHigher I-FABP and IgA levels to beta-lactoglobulin in children suggest increased intestinal permeability compared to adults. Only IgA to beta-lactoglobulin was significantly elevated in the children of mothers with GDM.